2020
DOI: 10.21873/invivo.12132
|View full text |Cite
|
Sign up to set email alerts
|

TGFBI Expression Predicts the Survival of Patients With Oropharyngeal Squamous Cell Carcinoma

Abstract: Background/Aim: This study was conducted to investigate transforming growth factor beta-induced protein (TGFBI) expression and analyze the clinical and prognostic significance of TGFBI in oropharyngeal squamous cell carcinoma (OPSCC). Patients and Methods: We evaluated TGFBI expression by immunohistochemistry in 94 patients with OPSCC. For comprehensive analysis, TGFBI expression was subdivided into tumor cell score (T), stroma score (S), and the sum of two scores (TS) calculated using H-score. Clinicopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Subsequently, researchers tried to employ TGFBI as a biomarker for cancer prognosis. In a study of 94 patients with oropharyngeal carcinoma, high TGFBI expression in tumor stroma was an independent prognostic factor even after statistical adjustment for age, gender, smoking status, stage, grade and treatment [21]. Cancer-speci c survival was signi cantly better for patients with no cytoplasmic TGFBI expression in clear cell renal cell carcinoma as well [22].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, researchers tried to employ TGFBI as a biomarker for cancer prognosis. In a study of 94 patients with oropharyngeal carcinoma, high TGFBI expression in tumor stroma was an independent prognostic factor even after statistical adjustment for age, gender, smoking status, stage, grade and treatment [21]. Cancer-speci c survival was signi cantly better for patients with no cytoplasmic TGFBI expression in clear cell renal cell carcinoma as well [22].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, researchers began to employ TGFBI as a biomarker for cancer prognosis. In a study of 94 patients with oropharyngeal carcinoma, high TGFBI expression in tumor stroma was an independent prognostic factor even after statistical adjustment for age, gender, smoking status, stage, grade and treatment [31]. Cancerspeci c survival was signi cantly better for patients with no cytoplasmic TGFBI expression in clear cell renal cell carcinoma as well [32].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β is highly expressed in many types of cancers and involves in a number of important biological events including extracellular matrix synthesis, cell growth, and cell differentiation [20], thus leading to tumor progression, invasion and metastasis [31]. Furthermore, TGF-β has been regarded as the marker that associated with prognosis of HNSCC patients [26-28], and which has been con rmed by KIM et al [29]. As the most abundant type in TGF-β family [21], TGF-β1 has been reported that it is related to the poor prognosis of many malignancies [21][22][23][24][25], including HNSCC.…”
Section: Discussionmentioning
confidence: 99%